Webinar Strategi Kepemimpinan Organisasi Pembelajaran sebagai Upaya Meningkatkan Kualitas Pendidikan di Yayasan Mekar Arum Kabupaten Bandung - Hani Hadiati Pujawardani; Santy Christinawati; Mohammad Hasan; Endang Komara; Agus Mulyanto (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity aims to improve the leadership competence of principals and teachers in learning organizations as an effort to realize the quality of education at Mekar Arum Foundation. This Community Service method uses counseling in the form of webinars. The target of this service is the principal, teachers and staff of Mekar Arum Bandung Kindergarten, Junior High School, and Senior High School. The evaluation instrument of this activity uses questionnaires and interviews which are then analyzed descriptively, the results of this service show that school principals have the competence to design, organize, direct, and coordinate staff within the context of learning organizations. Principals can design effective learning strategies, inspire staff, and create a positive learning climate in the school. Through a learning organization approach, it can make a significant contribution in improving the quality of education at Mekar Arum Foundation.